Respostas
respondido por:
1
Resposta:
D = - 8
Explicação passo-a-passo:
D = Diagonais principais - Diagonais secundárias
D = ((1 * -1 * 3) + (-2 * 1 * 2) + (-2 * 1 * 1)) - ((-2 * 1 * 3) + ( 1 * 1 * 1) + ( -2 * -1 * 2))
D = ( - 3 - 4 - 2) - ( - 6 + 1 + 4)
D = ( - 9) - ( -1 )
D = - 9 + 1
D = - 8
respondido por:
0
Resposta:
Explicação passo-a-passo:
D = 1(-1).3 + (-2).1.2 +1.1.(-2) - 2.(-1)(-2) -1.1.1 - (-2).3
= -3 -4 -2 - 4 - 1 + 6 = -8
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás